The most common end-of-life reflections: A survey of hospice and palliative nurses. Issue 4 (2nd April 2020) - Ent, Michael R.; Gergis, Mary A.
Abstract: To identify the most common end-of-life reflections among terminally ill patients, 124 nurses from the Hospice and Palliative Nurses Association (HPNA) completed an online, open-ended survey. Common themes of these reflections included concern for loved ones, regret, morbidity and mortality, gratitude, spirituality, legacy, and thoughts about acceptance or non-acceptance of impending death. Nurses reported that their patients were more concerned about their loved ones than their own morbidity and mortality. Common end-of-life reflections may serve as cues that hospice and palliative patients are self-initiating therapeutic life review.